2022
DOI: 10.1136/thoraxjnl-2021-218635
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related changes in outpatient CPAP setup pathways for OSA are linked with decreased 30-day CPAP usage

Abstract: The COVID-19 pandemic changed continuous positive airway pressure (CPAP) setup pathways. We evaluated patients commenced on CPAP in 2019 (prepandemic) and 2020 (post-first UK wave). Face-to-face (F2F) setup numbers, with CPAP turned on, decreased from 613 patients (98.9%) in 2019, to 6 (1.1%) in 2020. In 2020, setups were F2F without CPAP turned on (403 (71.1%)), or remote (158 (27.9%)). Prepandemic median CPAP usage at first follow-up was 5.4 (2.7–6.9) hours/night and fell by 0.9 hours/night (95% CI 0.5 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…They found that pre-pandemic median CPAP usage was 5.4 (2.7-6.9) h per night at the first follow-up and this fell by 0.9 h per night (95% CI 0.5-1.2, p<0.0001) in 2020. The authors state that they found clinically relevant reductions in CPAP usage with the pathway changes introduced post-COVID-19 [23]. Similar findings are reported in a study which allocated 666 patients to three pathways for PAP treatment initiation [24].…”
Section: Mitigation Strategies To Overcome the Lockdown Of Sleep Medi...supporting
confidence: 68%
See 1 more Smart Citation
“…They found that pre-pandemic median CPAP usage was 5.4 (2.7-6.9) h per night at the first follow-up and this fell by 0.9 h per night (95% CI 0.5-1.2, p<0.0001) in 2020. The authors state that they found clinically relevant reductions in CPAP usage with the pathway changes introduced post-COVID-19 [23]. Similar findings are reported in a study which allocated 666 patients to three pathways for PAP treatment initiation [24].…”
Section: Mitigation Strategies To Overcome the Lockdown Of Sleep Medi...supporting
confidence: 68%
“…However, there is evidence from studies that a remote start for PAP treatment is associated with reduced long-term compliance. A multicentre study in the UK compared the adherence rate with PAP treatment when started at a distance during the pandemic with historic data from 2018 and 2019, when PAP treatment was started during a face-to-face meeting [23]. They found that pre-pandemic median CPAP usage was 5.4 (2.7-6.9) h per night at the first follow-up and this fell by 0.9 h per night (95% CI 0.5-1.2, p<0.0001) in 2020.…”
Section: Mitigation Strategies To Overcome the Lockdown Of Sleep Medi...mentioning
confidence: 99%
“…This increase in CPAP usage is consistent with earlier meta-analyses which focused on the use of virtual care strategies specifically to investigate the effect on CPAP adherence [ 15 17 ]. However, recent post-COVID-19 data has shown a reduction in CPAP adherence with remote CPAP set-up, compared to in-person [ 11 , 35 ]. While CPAP set-up is just one part of the process of initiation onto therapy, these data highlight the need for robust assessment of new healthcare strategies before they become mainstream.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated by the coronavirus disease 2019 (COVID-19) pandemic [ 9 ], digital health interventions such as telemonitoring and virtual consultations have been introduced into sleep medicine to meet this growing demand [ 10 , 11 ]. Such transition has the potential to revolutionise the way healthcare is delivered, improving accessibility and affordability [ 12 ], though there are concerns about exacerbating inequalities, particularly in disadvantaged communities such as minorities and rural populations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of the COVID-19 pandemic, according to a multicenter study, the F2F setup decreased drastically from 98.9% prepandemic to 1.1% during the pandemic. The study shows a significant drop in CPAP adherence as well [ 86 ]. However, one single-center study shows successful implementation of remote diagnostic and treatment pathways for CPAP with similar adherence patterns to the F2F setup pathways [ 87 ].…”
Section: Managementmentioning
confidence: 99%